2016
DOI: 10.1016/j.celrep.2016.02.065
|View full text |Cite
|
Sign up to set email alerts
|

NLRX1 Acts as an Epithelial-Intrinsic Tumor Suppressor through the Modulation of TNF-Mediated Proliferation

Abstract: The mitochondrial Nod-like receptor protein NLRX1 protects against colorectal tumorigenesis through mechanisms that remain unclear. Using mice with an intestinal epithelial cells (IEC)-specific deletion of Nlrx1, we find that NLRX1 provides an IEC-intrinsic protection against colitis-associated carcinogenesis in the colon. These Nlrx1 mutant mice have increased expression of Tnf, Egf, and Tgfb1, three factors essential for wound healing, as well as increased epithelial proliferation during the epithelial regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 38 publications
3
51
0
Order By: Relevance
“…In addition to our current findings, prior studies have also evaluated NLRX1 in cancer utilizing either xenograft models or models of inflammation driven colorectal cancer [16, 17, 25, 26]. In the xenograft study, nude mice were injected with RKO colon carcinoma cells, where NLRX1 was either stably knocked down or overexpressed [16].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In addition to our current findings, prior studies have also evaluated NLRX1 in cancer utilizing either xenograft models or models of inflammation driven colorectal cancer [16, 17, 25, 26]. In the xenograft study, nude mice were injected with RKO colon carcinoma cells, where NLRX1 was either stably knocked down or overexpressed [16].…”
Section: Discussionmentioning
confidence: 78%
“…In the presence of TNF, NLRX1 knockdown resulted in significantly increased tumor volume, whereas overexpression attenuated tumor growth [16]. To evaluate the role of NLRX1 in CAC, tumorigenesis was induced in wild type and Nlrx1 −/− mice by treating the animals with the chemical carcinogen azoxymethane (AOM) immediately prior to dextran sulfate sodium (DSS) exposure [17, 25, 26]. In this model, inflammation associated with DSS exposure functions as a tumor promoter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, NLRX1 has been linked to the viral response, innate immunity and downstream effects on NF-κB signaling [47]. Located on the outer mitochondrial membrane, NLRX1 has been shown to influence reactive oxygen species production and the proliferation of epithelial cells in the context of colorectal cancer disease models [810]. As such, NLRX1 is a potential immunoregulatory molecule that integrates immune and metabolic function.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NLRX1 promotes virus-induced autophagy by interactions with another mitochondrial protein, TUFM (Tu translation elongation factor, mitochondrial) (30). Interestingly, two recent studies demonstrated that NLRX1 acts as a tumor suppressor to reduce tumorigenesis through regulating tumor necrosis factor (TNF) and IL-6 signaling pathways (31,32). However, the potential functions of NLRX1 in HCV propagation and the HCV-induced innate immune response remain unknown.…”
mentioning
confidence: 99%